Forward Position Solution of Redundantly Constrained Cable-driven Parallel Robot - Tao Ye; Zhang Shangying; Wang Yanwei (Jixie chuandong)
An algorithm for solving the forward position solution problem of the parallel robot based on Levenberg-Marquardt method is proposed. A kinematics model of a redundantly constrained cable-driven parallel robot is established，and the mechanism is parameterized to solve the inverse position solution problem. The nonlinear equations of forward kinematics are established，and the original pose of the end effector is taken as the iterative initial value to solve the forward position solution problem by applying the proposed algorithm. The Matlab/Simulink/xPC tool is used for simulation experiments. The complex periodic circular curve is selected as the motion trajectory of the parallel robot for the real-time simulation. It is verified that the algorithm can achieve accurate forward position solution and smooth motion trajectory，and has good real-time performance. Five pose combinations are selected to verify the high efficiency of the algorithm. The calculation results show that the algorithm has fewer iterations，shorter computation time and higher accuracy，which provides a theoretical guidance for real-time monitoring and complex control strategies of parallel robots.